1993
DOI: 10.1007/bf00029874
|View full text |Cite
|
Sign up to set email alerts
|

The high-molecular-weight glutenin subunit compositions of Chinese bread wheat varieties and their relationship with bread-making quality

Abstract: The composition of the high-molecular-weight (HMW) subunits of glutenin encoded by Glu-1 in hexaploid wheat (Triticum aestivum L.) was determined for 99 varieties bred in China . Seventy-nine varieties were homogeneous for HMW glutenin subunit composition . The majority of the remainder were heterogeneous at one Glu-I locus, with two varieties heterogeneous at two loci . One variety carried a pattern of subunits not encountered in previous studies . The majority of varieties, as in previous studies, carried su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
0
11
1
Order By: Relevance
“…The origin of the unusual HMW-GS in the Xiaoyanmai 7 endosperm was not resolved in an earlier study (Wang et al 1993), but the present experiments have shown unequivocally that they could not have been inherited from A. elongatum, a species that is represented in the pedigree of this cultivar. Instead, the evidence, based on a variety of assays, strongly implicated cereal rye as the progenitor.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The origin of the unusual HMW-GS in the Xiaoyanmai 7 endosperm was not resolved in an earlier study (Wang et al 1993), but the present experiments have shown unequivocally that they could not have been inherited from A. elongatum, a species that is represented in the pedigree of this cultivar. Instead, the evidence, based on a variety of assays, strongly implicated cereal rye as the progenitor.…”
Section: Discussioncontrasting
confidence: 73%
“…A major survey of the HMW-GS composition in Chinese bread wheat germplasm has identified an unusual profile in the cultivar Xiaoyanmai 7 (Wang et al 1993). A suggestion, based on pedigree information, was that the origin of the genes encoding these unusual HMW-GS was the wheat close relative Agropyron elongatum.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Lukow et al (1989) reported that almost all wheat lines encoding 2 + 12 at Glu-D1 had poor breadmaking quality and that subunit 5 + 10 was needed at this locus to provide adequate gluten strength for bread. Wang et al (1993) observed that within Glu-1, composition at subunits A1 and D1 accounted for the majority (≈86%) of variations in gluten strength as measured by a microsedimentation test. In our study, it was clear that the Glu-D1 allele encoding subunits 2 + 12 was a major contributor to desirable tortilla quality.…”
Section: Tortilla Propertiesmentioning
confidence: 93%
“…Thus, all wheat groups encoding for 2 + 12 at Glu-D1 produced good quality tortillas. Presence of 2 + 12 at Glu-D1 has been reported to weaken dough strength relative to 5 + 10 at the same domain (Lukow et al 1989;Wang et al 1993). In fact, Lukow et al (1989) reported that almost all wheat lines encoding 2 + 12 at Glu-D1 had poor breadmaking quality and that subunit 5 + 10 was needed at this locus to provide adequate gluten strength for bread.…”
Section: Tortilla Propertiesmentioning
confidence: 99%
See 1 more Smart Citation